The relationship between ECtHR and CJEU and national criminal courts in the light of the concept of human rights - Hinov, Ivo (Law Journal of New Bulgarian University, 2022)
The concept of human rights is at the heart of the relationship between the two supranational courts – ECtHR and the CJEU – and the national jurisdictions. This relationship is complex in nature involving both the perception of and opposition against the legal solutions adopted by supranational courts. But its result is clear – it affirms the human rights as super-right, a supreme imperative and a criterion for assessing the legality of national law and case law.